What does consent look like in early years?. (2nd September 2022) - Davies, Dawn
Abstract : Early years teacher, Dawn Davies explores the meaning of consent and how it has changed the ethos of her setting to value the voice of the unique child. Using intimate care as a focal point, she explores attitudes and factors that she experienced which shaped how her team has transformed the setting into one that places consent and wellbeing as the foundations of best practice.